2017
DOI: 10.1371/journal.pone.0173869
|View full text |Cite
|
Sign up to set email alerts
|

Treating major depression with yoga: A prospective, randomized, controlled pilot trial

Abstract: BackgroundConventional pharmacotherapies and psychotherapies for major depression are associated with limited adherence to care and relatively low remission rates. Yoga may offer an alternative treatment option, but rigorous studies are few. This randomized controlled trial with blinded outcome assessors examined an 8-week hatha yoga intervention as mono-therapy for mild-to-moderate major depression.MethodsInvestigators recruited 38 adults in San Francisco meeting criteria for major depression of mild-to-moder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
117
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(121 citation statements)
references
References 163 publications
(140 reference statements)
2
117
1
1
Order By: Relevance
“…In terms of mental health, yoga has shown to be an effective treatment for those suffering from clinically diagnosed major depression [8,9]. Studies have also shown that yoga can improve both physical and mental health in a variety of generally healthy yet diverse populations [10,11,12].…”
Section: Exercise Medicinementioning
confidence: 99%
“…In terms of mental health, yoga has shown to be an effective treatment for those suffering from clinically diagnosed major depression [8,9]. Studies have also shown that yoga can improve both physical and mental health in a variety of generally healthy yet diverse populations [10,11,12].…”
Section: Exercise Medicinementioning
confidence: 99%
“…There is a growing body of evidence that supports the use of yoga practice in the treatment of psychiatric diseases. While metanalyses of RCTs present some methodological drawbacks, yoga could be considered an effective add‐on treatment option for depressive patients, resulting in a significant reduction in depression severity scores, ruminative thoughts, and depressive manifestations. These approaches have also been determined effective in pregnant women …”
Section: Focus On Mental Health and Stress Management: Clinical Effecmentioning
confidence: 99%
“…The Beck Depression Inventory, created by Aaron T. Beck, is a 21-question multiple-choice self-report inventory, one of the most widely used psychometric tests for measuring the severity of depression. This is a Likert type self-reported scale that consists of 21 items (7,8). This scale measures and identifies emotional, cognitive, physical, and motivational symptoms of depression objectively.…”
Section: Instrumentsmentioning
confidence: 99%
“…8 In addition to the gynaecological, endocrine and metabolic features of PCOS, a number of psychological correlates have been identified. Quality of life and psychological well-being are reduced in women with PCOS (Elsenbruch et al, Coffey et al and Barnard et al).…”
Section: Introductionmentioning
confidence: 99%